Misión a Patagonia - Coppa, Rafael Carlos; Saccone, E.; Bandieri, Bernardo Hugo; Cecchetto, Aldo Mario (Comisión Nacional de Energía Atómica; Argentina, 1971)
Fil: Coppa, Rafael Carlos Comisión Nacional de Energía Atómica; Argentina